Sustainable and Optimized Utilization of Water Resources: Inflatable Dams Potential in Pakistan: Sustainable Utilization of Water Resources - Rashid, Muhammad Usman; Latif, Abid; Ghani, Usman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Development of new reservoirs are utmost important for their utilization of providing water for irrigation, hydropower and flood damages reduction etc. In-addition to constructing new reservoirs, the efficient and sustainable use of existing reservoirs is also important for rapid economic growth of world. Pakistan is blessed with rich surface water resources of 180 Billion m3 annualy. However, total storage capacity of the three large dams is 17 Billion m3 which is only 10% of the available water resources. The current study identifies the latest trends for optimizing the utilization of water from reservoir to agriculture farm and their possible application to Pakistan. The paper also investigates the potential of inflatable dams in Pakistan for recharging of groundwater, as diversion weir for small hydropower plants, water supply and creating artificial lakes for recreation purposes. On the basis of criteria developed in the study, 31 sites were selected for checking their feasibility. SRTM 90m digital elevation database and Google Mapper were used to develop digital elevation models and contours for studying different technical parameters. Total 27 sites were found feasible and indicated the potential for Inflatable Dams in Pakistan on the basis of preliminary results. For sustainable and optimized utilization of water resources, it is utmost important to implement the following measures identified for supplying water from reservoir to crop root zone are: remodeling/ modernization of barrages and canals including lining of distributaries and minors. Adoption of resource conservation technologies, and optimized cropping systems by including high value and high yield crops are recommended in the study for achieving the desired objectives.